2023
DOI: 10.1002/iid3.776
|View full text |Cite
|
Sign up to set email alerts
|

Ononin alleviates DSS‐induced colitis through inhibiting NLRP3 inflammasome via triggering mitophagy

Abstract: Background: Ononin, a flavonoid isolated from Astragalus membranaceus root, is the active ingredient of A. membranaceus and has potential anti‐inflammatory properties, but its effect on colitis is unclear. Aims: This study aimed to explore the anticolitis effect of Ononin by establishing a colitis model in mice induced by dextran sulfate sodium (DSS). Methods: Male C57BL/6 mice were provided DSS, then treated with Ononin (10, 20, 40 mg/kg) or 5‐ASA (40 mg/kg). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Not only does HJXJ reduce the loss of renal units by inhibiting pyroptosis, but it can also minimize additional tissue damage caused by the inflammatory environment. Interestingly, components of HJXJ, such as Astragalus mongolicus , Rhizoma coptis chinensis , and Centella asiatica , have shown anti-inflammatory effects and are involved in regulating the inflammasome pathway [ 51 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Not only does HJXJ reduce the loss of renal units by inhibiting pyroptosis, but it can also minimize additional tissue damage caused by the inflammatory environment. Interestingly, components of HJXJ, such as Astragalus mongolicus , Rhizoma coptis chinensis , and Centella asiatica , have shown anti-inflammatory effects and are involved in regulating the inflammasome pathway [ 51 , 73 , 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, triggering mitochondrial autophagy is a potential strategy for treating inflammatory diseases. [ 40 ] Studies have also found that flavonoids exhibit a strong inhibitory effect on liver fibrosis by inhibiting NF-κB and various downstream inflammatory factors. [ 41 ] Astragaloside IV may regulate the differentiation of activated CD4 + subset T cells (including Th 1, Th 17, and Treg) through JAK/STAT and NF-κB signaling, induce the apoptosis of activated CD4 T cells, and ultimately significantly reduce the demyelination and inflammatory infiltration in the central nervous system of mice with autoimmune encephalomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…TEM showed that the number of autophagosomes increased in lutein-treated IEC-6 cells[ 8 ]. In addition, several Chinese herbs such as ononin, celastrol, licorice, and Jianpi-Qingchang decoction have been shown to protect IECs and treat experimental colitis by activating mitophagy[ 85 - 88 ]. Subsequently, Truzzi and colleagues demonstrated that stimulation of autophagy by a combination of spermidine and eugenol supplements reduced intestinal inflammatory parameters[ 89 ].…”
Section: Autophagy and Gi Diseasesmentioning
confidence: 99%